2000
DOI: 10.1097/00005537-200011000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Surfactant Aerosol Therapy for Otitis Media With Effusion

Abstract: Objective: To determine the effect of surfactant alone and with other medications delivered intranasally as a metered dose inhaler (MDI) aerosol on the resolution of experimentally induced otitis media with effusion (OME). Background: Eustachian tube dysfunction is a primary factor in the pathogenesis of OME. Intranasal surfactant via MDI has been shown in this laboratory to reduce passive opening pressure of the eustachian tube in normal gerbils and mice. Study Design: OME was developed in 35 gerbils by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Native SP-B, isolated from human bronchioalveolar lavage fluid, killed clinical isolates of gram-positive and gram-negative bacteria in a dose-dependent manner [20]. The current experiments demonstrated that aerosolized metered dose inhalant delivery of synthetic surfactant was effective in reducing passive opening pressure in the animal with OME or acute otitis media [2][3][4]. This surfactant is a synthetic phospholipids without protein.…”
Section: Discussionmentioning
confidence: 58%
“…Native SP-B, isolated from human bronchioalveolar lavage fluid, killed clinical isolates of gram-positive and gram-negative bacteria in a dose-dependent manner [20]. The current experiments demonstrated that aerosolized metered dose inhalant delivery of synthetic surfactant was effective in reducing passive opening pressure in the animal with OME or acute otitis media [2][3][4]. This surfactant is a synthetic phospholipids without protein.…”
Section: Discussionmentioning
confidence: 58%
“…SP-B was recently shown to share features with antimicrobial peptides, and native SP-B isolated from human bronchioalveolar lavage fluid was demonstrated to kill clinical isolates of gram-positive and gram-negative bacteria in a dose-dependent manner (26). Inhalation delivery of an aerosolized metered dose of synthetic surfactant comprised of phospholipid and protein is effective in reducing the POPs in animals with OME or acute otitis media (10-12). The primary function of the synthetic surfactant is obviation of adhesion (12).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous natural (7-9) and synthetic (10-12) surfactant preparations can reduce the passive opening pressure (POP), which is the pressure required to force the Eustachian tube open. Over 90% of the known surfactants are phospholipids whose chemical structure possesses both a hydrophilic and hydrophobic character in different regions of the compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flisberg et al suggested that the presence of surface, tension‐lowering substances (surfactants) might influence the function of the ET. Several recent studies have investigated the efficacy of surfactant therapy on the resolution of OME . These studies were conducted by inducing acute OME experimentally with a bacterial agent, administering surfactant on a periodic basis, and observing the resolution time.…”
Section: Introductionmentioning
confidence: 99%